cAMP signalling meets mitochondrial compartments. - Lefkimmiatis, K (Portland Press Ltd, 2014)
Mitochondria are highly dynamic organelles comprising at least three distinct areas, the OMM (outer mitochondrial membrane), the IMS (intermembrane space) and the mitochondrial matrix. Physical compartmentalization allows these organelles to host different functional domains and therefore participate in a variety of important cellular actions such as ATP synthesis and programmed cell death. In a surprising homology, it is now widely accepted that the ubiquitous second messenger cAMP uses the same stratagem, compartmentalization, in order to achieve the characteristic functional pleiotropy of its pathway. Accumulating evidence suggests that all the main mitochondrial compartments contain segregated cAMP cascades; however, the regulatory properties and functional significance of such domains are not fully understood and often remain controversial issues. The present mini-review discusses our current knowledge of how the marriage between mitochondrial and cAMP compartmentalization is achieved and its effects on the biology of the cell.